2010
DOI: 10.1097/sla.0b013e3181d3d3da
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Costs of Donation After Cardiac Death Liver Transplantation

Abstract: Higher rates of graft failure and biliary complications translate into markedly increased direct medical care costs for DCD recipients. These important financial implications should be considered in decisions regarding the use of DCD livers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 16 publications
2
83
2
Order By: Relevance
“…Other investigators have also seen significantly higher rates of ischemic cholangiopathy in DCD liver transplant recipients. (4,16,17) For these reasons, many transplant centers have shied away from using DCD livers.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also seen significantly higher rates of ischemic cholangiopathy in DCD liver transplant recipients. (4,16,17) For these reasons, many transplant centers have shied away from using DCD livers.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that patient and graft survival rates were not different between DCD and DBD grafts in the aforementioned study. Similarly, Jay and associates 48 found increased 1-year posttransplant costs for DCD recipients (125% of DBD cost). The cost remained higher in DCD (120% of DBD) transplants despite the exclusion of retransplants, which is a major risk for DCD livers but occurs infrequently.…”
Section: Emre a Eren Et Al/experimental And Clinical Transplantationmentioning
confidence: 99%
“…Relevant to this investigation, Jay and coworkers estimated direct medical care costs based on inpatient and outpatient care for 28 DCD and 198 DBD liver recipients. 30 They found that the mean 1-year posttransplant costs were higher for DCD recipients (124.9% DBD costs; P = .04; 95% CI = 102%-151%). Furthermore, the increased DCD costs persisted (125.2% DBD costs; P = .009; 95% CI = 106%-144%) after adjustment for recipient characteristics (age, sex, race, body mass index, Model For End-Stage Liver Disease [MELD] score, hepatitis C, hepatocellular carcinoma, and medical status).…”
Section: Donation After Cardiac Death Costs and Resource Utilizationmentioning
confidence: 99%
“…6,[12][13][14][16][17][18]25,[28][29][30] Foley and coworkers 13 reported that rates of overall biliary complications (DCD, 47%; DBD, 26%; P < .01) and IC (DCD, 34%; DBD, 1%; P < .01) were significantly higher in the DCD group. Research conducted by Chan and associates 28 indicated no incidence of PNF from DCD allografts.…”
Section: Complications Of Livers From Donation After Cardiac Death Domentioning
confidence: 99%